The Observation of Imperfections in Medical Implants by Holographic Interferometry and the Comparisons of These Observations to Other Methods - Abali, Baran; Demircali, Ali Anil; Uvet, Huseyin (IEEE, 2017)
The purpose of this study is to be able visually display and discuss the possible issues faced with medical implants in patients, by the use of holograph. Although this issue can be solved in many different ways, the object of this study aims to use current technology in order to facilitate the use of holograph technology, which can easily be used in classroom or home settings, in order to be able to assess the stability of the testing method at hand. With this method, it is easy to assess the reasoning behind the shortened lifespan of an implant by optically comparing its original state to its current state. We can also see that the use of holographic technology is 100 times more cost-effective and easy to apply than other conventional methods. The main axis of this method shows us holographic interferometry utilizing interference pattern made up of constructive and destructive waves. This study focuses highly on this method of utilizing technology that can easily turn even mobile phones into laboratories by concentrating on image processing technology, in turn creating an interface which can meet the needs of many researchers. With this study, it will be possible to create high-quality, cost-effective, and user-friendly test devices, which can be used in order to educate and fabricate.
Keywords: holography interferometry; biomedical devices; image processing; DIGITAL HOLOGRAPHY; Engineering